Simulation of the thermomechanical effects originated on a fuel pin with a creacked pellet by different power ramp velocities, using a two dimensional finite element model - Basombrío, Fernando G. (North Holland Publishing Company, 1982)
Fil: Basombrío, Fernando G. Comisión Nacional de Energía Atómica; Argentina